Introduction to internal medicine - Mlíková Seidlerová, Jitka; King, Jeremy; Holá, Alena (Stanislav Juhaňák - Triton, 2020)
Textbook for students and doctors, which focuses on diagnostic methods in internal medicine.
Keywords: Internal Medicine; diagnostika; diagnostické techniky a postupy; Diagnostic Techniques and Procedures; vnitřní lékařství